Use of 18F-FDG PET/CT to Differentiate Ectopic Adrenocorticotropic Hormone-Secreting Lung Tumors From Tumor-Like Pulmonary Infections in Patients With Ectopic Cushing Syndrome - Hou, Guozhu; Jiang, Yuanyuan; Li, Fang; Cheng, Xin (Frontiers in Oncology, 2021)
Background Ectopic adrenocorticotropic hormone (ACTH)-secreting lung tumors represent the most common cause of ectopic Cushing syndrome (ECS). Pulmonary opportunistic infections are associated with ECS. The present study aimed to evaluate the usefulness of 18F-FDG PET/CT for differentiating ectopic ACTH-secreting lung tumors from tumor-like pulmonary infections in patients with ECS. Methods We retrospectively reviewed the imaging data of 24 patients with ECS who were suspected to have ACTH-secreting lung tumors and underwent 18F-FDG PET/CT between 2008 and 2019. Eleven patients with lung tumors and 4 with pulmonary infections also had additional somatostatin receptor imaging (99mTc-HYNIC-TOC SPECT/CT or 68Ga-DOTATATE PET/CT). Results In total, 18 patients had lung tumors and six had pulmonary infections. The primary source of ECS remained occult in the six patients with pulmonary infections. The maximum standardized uptake value (SUVmax) for pulmonary infections was significantly higher than that for tumors (P = 0.008). Receiver operating characteristic analysis revealed that a cut-off SUVmax of 4.95 helped in differentiating ACTH-secreting lung tumors from infections with 75% sensitivity and 94.4% specificity. For the 11 patients with ACTH-lung tumors, somatostatin receptor imaging (SRI) was positive in 6; while for the 4 with pulmonary infections, SRI was positive in 2. The sensitivity and specificity of somatostatin receptor imaging (SRI) for detecting ACTH-secreting lung tumor was 54.5% and 50%. Conclusions Our findings suggest that pulmonary infections exhibit significantly higher FDG uptake than ACTH-secreting lung tumors in 18F-FDG PET/CT. An SUVmax cut-off value of 4.95 may be useful for differentiating the two conditions. Our results also suggested that SRI may not be an effective tool for differentiating the two conditions given the relatively low specificity.